Indonesian Language Politeness Counseling for Early Childhood Character Education in Tompobalang: Penyuluhan Kesantunan Berbahasa Indonesia untuk Pendidikan Karakter Anak Usia Dini di Tompobalang - Munira Hasjim; Lukman Lukman; Tadjuddin Maknun; Kaharuddin Kaharuddin; Ita Suryaningsi; Muhammad Sunre; Indarwati Indarwati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Indonesian Language Politeness Education for Character Building in Early Childhood in Tompobalang was conducted due to the importance of character development from an early age through the use of polite language. Considering the role of mothers as the primary educators at home, this program targeted members of the Majelis Taklim Association (Permata) in Tompobalang, Somba Opu District, Gowa Regency. The methods used in this community service included lectures, interactive discussions, and simulations. The program aimed to increase the awareness and ability of mothers to apply polite language in their daily communication with their children. The results showed an increase in the understanding and awareness of mothers about the importance of polite language in shaping children's character. Additionally, the mothers became more skilled in using appropriate and polite language. In conclusion, this program significantly contributes to character building in children through the active role of mothers in communicating with polite language